Preliminary Study of Chemistry Knowledge Through Ethnochemistry Approaches to Communities - Ade P. Maedja; Purnama Ningsih (Universitas Tadulako, 2021)
This research was a descriptive qualitative study using ethnographic methods. It aimed to determine the understanding and application of chemistry knowledge in the daily lives of Wiapore society, Marawola Barat district, through an ethnochemistry approach. Data obtained was in the form of an initial data inventory. These inventory data were then grouped into several data categories, namely categories related to food, beverage, and agriculture categories. The percentage value of each data was as follows, related to food 55.55%, related to drinks were 22.22%, and connected to agriculture were 22.22%. The results of this study are significant for local governments in taking policies relating to education for children and the Wiapore community